2014
DOI: 10.5817/bse2014-1-3
|View full text |Cite
|
Sign up to set email alerts
|

English discourse markers in mediatised political interviews

Abstract: The present case study takes a discourse-pragmatic approach to some of the most frequently used discourse markers (henceforth DMs) in spoken English: I mean, of course, oh, well, I think and you know. The point of departure in this research is a set of discourse-pragmatic relations and functions, such as conversation management, thematic control, concession, elaboration, reformulation, ventriloquizing, and marking evidentiality. After looking at which DMs signal these relations and functions in our corpora, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 27 publications
1
11
0
1
Order By: Relevance
“…The results were in line with Carter and McCarthy's (2006) claim that DMs occur more often in spoken than in written language. The findings also agreed with Furko and Abuczki (2014) that DMs are genre-dependent. DMs occur more frequently in spoken than in written language; that is, the more interactive the genre is, the more frequently DMs occur (Huang, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…The results were in line with Carter and McCarthy's (2006) claim that DMs occur more often in spoken than in written language. The findings also agreed with Furko and Abuczki (2014) that DMs are genre-dependent. DMs occur more frequently in spoken than in written language; that is, the more interactive the genre is, the more frequently DMs occur (Huang, 2011).…”
Section: Discussionsupporting
confidence: 80%
“…He notes that they can presage ‘transformative answers’ which reframe the question that was asked (see also Stivers and Hayashi, 2010, and Clayman’s 1993a study of evasive answers in televised news interviews). In the study of political interviews, Furkó and Abuczki (2014) argue that ‘well’ can be used to presage a topic shift.…”
Section: Discussionmentioning
confidence: 99%
“…Furkó, 2013;Furkó and Abuczki, 2014;Furkó et al, forthcoming), and reconsiders those findings from the perspective of influencing intentions in general and manipulative intent in particular. The aim is to associate different groups of PrMs (evidential markers, general extenders, quotation markers and so on) with particular manifestations of manipulative intent identified in the relevant CDA research, such as suppression, polarization, recontextualising and conversationalisation.…”
Section: Methodsmentioning
confidence: 99%
“…The genrebased analysis of political news interviews and celebrity interviews (cf. Furkó, 2013;Furkó and Abuczki, 2014) revealed that the functional spectrum of PrMs in celebrity interviews is in many ways similar to that in spontaneous informal conversations, while PrMs fulfil fewer interactional and more heteroglossic functions in more prototypical political news interviews. However, on the basis of the analysis of manipulative uses, we can make further refinements to the distributional patterns of PrMs.…”
Section: Prms Marking Manipulative Intent In Political Interviewsmentioning
confidence: 99%